Application of iron–carbon microbial galvanic activated sludge combined with MBR process in the treatment of wastewater from comprehensive railway station - Zhang, Qi; Liang, Zheng; Guan, Xiaotao; Liang, Jingwen; Gao, Pan (Frontiers in Environmental Science, 2022)
The application of iron–carbon microbial cell activated sludge (ICMC-AS) was carried out in a membrane bioreactor (MBR) processor to treat wastewater from an integrated railway station. Results showed that the chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP) removal efficiencies of the original MBR processor increased from 80%, 30%, and 10% to 92%, 93.5%, and 92%, respectively. Further research showed that the combined sewage treatment system also had a strong impact resistance ability. The combined sewage treatment system ran stably when the COD, TN, and TP concentrations changed greatly. The in-depth analysis of the reaction process and reaction rate of the combined sewage treatment system revealed that the combined system is dominated by COD removal with high nitrogen removal efficiency. The removal rate constants of various pollutants were in the order: KCOD (0.647 ± 0.017) > KNO3−−N (0.416 ± 0.044) > KNH4+−N (0.275 ± 0.014) > KTN (0.258 ± 0.083). Calculations of the energy saving and carbon emission reduction of the combined system showed that the system’s annual carbon emission reduction could reach more than 388,203.55 kg CO2e, which remarkably improves the carbon emission reduction effect and obtains a good green effect. The results indicate that adding ICMC-AS to the MBR processor for combined wastewater treatment can substantially improve the efficiency of wastewater treatment and obtain better energy-saving and emission-reducing effects. This combined application provides an effective way for the transformation and upgrading of small- and medium-scale water treatment systems.